(3SMQ GdHdGZI hedM GdHQGYIs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GLRd GdehgHI Yf habg dMeOg hQVi Gddg JYGdi Yf CHj HcQ hYeQ hYKeGf GdCFeI GdCHQGQ s
(3BNQgG (B:s
(3hdh Cecfg Cf jSJbHdg dcGf Ydi Pdc MQjUkG eKGHQkG hdeG GSJbQ Ydjg GdSdGe TeN Ydi GdHdGOR ghkG hGNJjGdkG Je HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs